Biomechanical variables associated with Achilles-Tendinopathy in runners - Azevedo, L. B.; Lambert, M. I.; Vaughan, C. L.; O`Connor, C. M.; Schwellnus, M. P. (British Journal of Sports Medicine, 2009)
Objective: The aim of this study was to investigate the kinetics, kinematics and muscle activity in runners with Achilles tendinopathy. Design: Case-control study. Setting: Biomechanics laboratory. Participants: 21 runners free from injury and 21 runners with Achilles tendinopathy performed 10 running trials with standardised running shoes. Injured runners were diagnosed clinically according to established diagnostic criteria. Uninjured runners had been injury-free for at least 2 years. Main outcome measurements: During each trial, kinetic and lower limb kinematic data were measured using a strain gauge force plate and six infrared cameras respectively. Electromyographic (EMG) data from six muscles (tibialis anterior (TA), peroneus longus (PE), lateral gastrocnemius (LG), rectus femoris (RF), biceps femoris (BF) and gluteus medius (GM)) were measured with a telemetric EMG system. Results: Knee range of motion (heel strike to midstance) was significantly lower in injured runners than in uninjured runners. Similarly, preactivation (integrated EMG (IEMG) in 100 ms before heel strike) of TA was lower for injured runners than uninjured runners. RF and GM IEMG activity 100 ms after heel strike was also lower in the injured group. However, impact forces were not different between the two groups. Conclusion: Altered knee kinematics and reduced muscle activity are associated with Achilles tendinopathy in runners. Rehabilitation exercises or other mechanisms (e.g. footwear) that affect kinematics and muscle activity may therefore be beneficial in the treatment of runners with Achilles tendinopathy.